Gene therapy and its implications in Periodontics - Mahale Swapna; Dani Nitin; Ansari Shumaila; Kale Triveni (Wolters Kluwer Medknow Publications, 2009)
Gene therapy is a field of Biomedicine. With the advent of gene therapy in dentistry, significant progress has been made in the control of periodontal diseases and reconstruction of dento-alveolar apparatus. Implementation in periodontics include: -As a mode of tissue engineering with three approaches: cell, protein-based and gene delivery approach. -Genetic approach to Biofilm Antibiotic Resistance. Future strategies of gene therapy in preventing periodontal diseases: -Enhances host defense mechanism against infection by transfecting host cells with an antimicrobial peptide protein-encoding gene. -Periodontal vaccination. Gene therapy is one of the recent entrants and its applications in the field of periodontics are reviewed in general here.